Linking Complement Activation, Coagulation, and Neutrophils in Transplant-Associated Thrombotic Microangiopathy - Gavriilaki, Eleni; Chrysanthopoulou, Akrivi; Sakellari, Ioanna; Batsis, Ioannis; Mallouri, Despina; Touloumenidou, Tasoula; Papalexandri, Apostolia; Mitsios, Alexandros; Arampatzioglou, Athanasios; Ritis, Konstantinos; Brodsky, Robert Alan; Mitroulis, Ioannis; Anagnostopoulos, Achilles (Thrombosis and Haemostasis, 2019)
Transplant-associated thrombotic microangiopathy (TA-TMA) is a severe and life-threatening complication of hematopoietic cell transplantation (HCT) that often coincides with graft-versus-host-disease (GVHD). Although endothelial damage seems to be the common denominator for both disorders, the role of complement system, neutrophils, and coagulation has not been clarified. In an effort to distinguish the pathogenesis of TA-TMA from GVHD, we evaluated markers of complement activation, neutrophil extracellular trap (NET) release, endothelial damage, and activation of coagulation cascade in the circulation of patients with these two disorders, as well as control HCT recipients without TA-TMA or GVHD. We observed that the terminal complement product C5b-9 levels, the levels of markers of NET formation, and thrombin–antithrombin complex levels were significantly increased in the TA-TMA group compared with patients without complications, whereas there was no significant difference between the GVHD and the control group. On the other hand, the levels of circulating thrombomodulin, an endothelial damage marker, were significantly increased in both TA-TMA and GVHD patients. These findings propose a role for the interplay between complement system, neutrophil activation through NET release, and activation of the coagulation cascade in TA-TMA.
Keywords: thrombotic microangiopathy; hematopoietic cell transplantation; graft-versus-host disease; complement; neutrophil extracellular traps